2011
DOI: 10.4314/acsj.v18i2.65795
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Ethiopian coriander accessions for agronomic and quality traits

Abstract: Coriander (Coriandrum sativum L.) is an annual spice herb that belongs to the family of Umbelliferae/Apiaceae. Although Ethiopia is known as a primary diversity for coriander, the knowledge on nature and extent of variation of the indigenous germplasm is limited. Hence, to address the nature and extent of variability on agronomic and chemical traits, test trial was conducted at Kokate and Wondo Genet, Southern Ethiopia, using 49 accessions arranged in randomised complete block design in two replications during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 8 publications
15
17
0
Order By: Relevance
“…This indicates that environmental variance (σ 2 e) had its own contribution on the performance of the traits in addition to genotypic variance. In line with this Mengesha and Alemaw (2010) reported a higher value of genotypic coefficient of variability for most of the traits in Ethiopian coriander accessions except for days to maturity, 100-seed weight and plant height. Petros (2008) also reported a wide range of variability among niger (Guizotia abyssinica) particularly from those that were collected from Wello and Hararge for days to maturity, plant height, days to 50% flowering and days to flowering initiation.…”
Section: Discussionsupporting
confidence: 77%
“…This indicates that environmental variance (σ 2 e) had its own contribution on the performance of the traits in addition to genotypic variance. In line with this Mengesha and Alemaw (2010) reported a higher value of genotypic coefficient of variability for most of the traits in Ethiopian coriander accessions except for days to maturity, 100-seed weight and plant height. Petros (2008) also reported a wide range of variability among niger (Guizotia abyssinica) particularly from those that were collected from Wello and Hararge for days to maturity, plant height, days to 50% flowering and days to flowering initiation.…”
Section: Discussionsupporting
confidence: 77%
“…Bhandari and Gupta (1993) reported thousand seed weight range of 5-22.1 g in coriander. Mengesha and Alemaw (2010) reported 9.8-12.8 g thousand seed weight range in coriander genotypes. Similarly, Cosge et al, (2009) reported 3.57-15.72 g range in thousand seed weight in sweet fennel.…”
Section: Resultsmentioning
confidence: 99%
“…Critical evaluation of available selections of improved types with high yield potential/ traits is of great value to the breeder for crop improvement (Moniruzzaman, 2013). Mengesha and Getinetalemaw (2010) evaluated some Ethiopian coriander genotypes and reported that identification and evaluation of elite or promising genotypes for yield and quality is an important crop improvement strategy. Giridhar (2009, 2011) opined that it is possible to realize 1500 kg ha -1 under rainfed conditions if a proper combination of genotypes and management are available to the farmers.…”
Section: Introductionmentioning
confidence: 99%